(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2013)
The article deals with the reception of Hölderlin in the George-circle, especially the editorial and scientific work of Norbert von Hellingrath. At the end the consequences of this approach until our days are discussed especially with Martin Heidegger.